Success rate of microsatellite instability examination and complete response with pembrolizumab in biliary tract cancer. Issue 6 (21st May 2021) - Kai, Yugo; Ikezawa, Kenji; Takada, Ryoji; Daiku, Kazuma; Maeda, Shingo; Abe, Yutaro; Yamai, Takuo; Fukutake, Nobuyasu; Nakabori, Tasuku; Uehara, Hiroyuki; Nagata, Shigenori; Wada, Hiroshi; et al.
Abstract: Background and Aim: The success rate of microsatellite instability (MSI) examination in biliary tract cancer (BTC) and the treatment outcomes of pembrolizumab in patients with MSI‐high (MSI‐H) BTC have not been fully investigated. We examined the success rate of MSI examination and the rate of MSI‐H status in patients with BTC as well as the treatment outcomes of patients with MSI‐H status who underwent pembrolizumab treatment. Methods: We retrospectively reviewed 60 consecutive patients with unresectable or postoperative recurrent BTC who underwent MSI examination in a Japanese cancer referral center between January 2019 and September 2020. Results: The study included 24 intrahepatic cholangiocarcinomas, 12 hilar cholangiocarcinomas, 4 distal cholangiocarcinomas, 16 gallbladder carcinomas, and 4 ampullary carcinomas. The methods of cancer tissue sampling were percutaneous liver tumor biopsy in 26 cases, surgery in 15 cases, endoscopic ultrasound fine‐needle aspiration in 12 cases, transpapillary bile duct biopsy in 5 cases, and others in 2 cases. The success rate of MSI examination was 98.3% (59 of 60). MSI examination failed in only one case using a surgical specimen due to time‐dependent degradation of DNA. The frequency of MSI‐H BTC was 3.3% (2 of 60 cases). One patient with MSI‐H intrahepatic cholangiocarcinoma achieved a complete response with pembrolizumab treatment. Conclusions: MSI examinations in BTC were successful in almost all cases, regardless of tissue sampling methods. We experienced a case in which pembrolizumab resulted in a complete response to MSI‐H BTC. Since pembrolizumab for MSI‐H BTC could prolong survival time, MSI examination should be performed proactively to increase treatment options. Abstract : We retrospectively reviewed 60 consecutive patients with advanced biliary tract cancer (BTC) who underwent microsatellite instability (MSI) examination. MSI examinations were successful in almost all cases (59 of 60 cases), regardless of tissue sampling methods including endoscopic ultrasound fine‐needle aspiration and liver tumor biopsy. The frequency of MSI‐high (MSI‐H) was 3.3%, and we experienced a case in which pembrolizumab resulted in a complete response to MSI‐H BTC.